2018
DOI: 10.3389/fimmu.2018.01218
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1 for Predicting Sepsis Severity and Mortality Outcomes: A Systematic Review and Meta-Analysis

Abstract: ObjectivesPlasminogen activator inhibitor-1 (PAI-1), a crucial regulator of fibrinolysis, is increased in sepsis, but its values in predicting disease severity or mortality outcomes have been controversial. Therefore, we conducted a systematic review and meta-analysis of its predictive values in sepsis.MethodsPubMed and Embase were searched until August 18, 2017 for studies that evaluated the relationships between PAI-1 levels and disease severity or mortality in sepsis.ResultsA total of 112 and 251 entries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 40 publications
0
54
1
Order By: Relevance
“…UFH has been indicated to exert an anticoagulant effect by binding to the lysine site on AT, which is also modulated by platelets, fibrin, thrombin, factors Xa, IXa, XIa and XIIa and TF (30,31). Tipoe (8) demonstrated that high levels of PAI-1 may predict an adverse outcome in severe sepsis, and suppressed fibrinolysis has been suggested to be one the most important predictors of multiple organ dysfunction during DIC. The results of the present study identified that preconditioning UFH attenuated the level of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UFH has been indicated to exert an anticoagulant effect by binding to the lysine site on AT, which is also modulated by platelets, fibrin, thrombin, factors Xa, IXa, XIa and XIIa and TF (30,31). Tipoe (8) demonstrated that high levels of PAI-1 may predict an adverse outcome in severe sepsis, and suppressed fibrinolysis has been suggested to be one the most important predictors of multiple organ dysfunction during DIC. The results of the present study identified that preconditioning UFH attenuated the level of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of fibrinolysis is mediated by plasminogen activators and is regulated by plasminogen activator inhibitor-1 (PAI-1). PAI-1, which indicates poor patient prognosis in sepsis-induced DIC, mediates the inhibition of endogenous fibrinolysis during sepsis (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of PAI-1 was found in cells in the heart tissue samples, suggesting that a reduced removal of fibrin may occur, leading to a deposition of fibrin clots in small blood vessels and inadequate tissue perfusion and organ failure (Brandtzaeg et al, 1990;Madoiwa et al, 2006). Previous studies indicate that elevated PAI-1 in plasma or serum is a significant predictor of disease severity and mortality, first discovered in plasma samples from meningococcal sepsis patients (Brandtzaeg et al, 1990;Kornelisse et al, 1996;Tipoe et al, 2018).…”
Section: Transcriptional Profiles In Heart Tissue Samplesmentioning
confidence: 99%
“…Because the occurrence and development of sepsis is closely related to the immune function of the body (Tipoe et al 2018), we compared the immune function related indicators of the patients. CD4+ expression in MG and SG patients was lower than that in CG patients, whereas CD8+ expression was higher.…”
Section: Discussionmentioning
confidence: 99%